Investigating the Transportation Economics of the Eastern Economic Corridor in Thailand - Tantiwat, Waranan (Journal of Applied Economics and Management Strategy, 2025)
This paper investigates the transportation economics of Thailand's Eastern Economic Corridor (EEC), highlighting significant challenges and potential solutions. Rapid economic development and increased industrial activities in the EEC have led to problematic transportation issues, including traffic congestion and environmental degradation. This study examines the interplay of supply and demand, opportunity costs, and externalities in the context of EEC's transportation challenges. Three economic solutions are explored: congestion pricing, Pigouvian environmental taxes, and subsidies for non-substitutable modes. Congestion pricing, successfully implemented in cities like London and Singapore, aims to reduce traffic by charging fees during peak hours, thus internalizing the external costs of driving. Pigouvian taxes, such as those in Sweden and British Columbia, target vehicle emissions to align private costs with social costs, encouraging cleaner transportation alternatives. Subsidies are proposed to promote the use of less polluting transport modes, shifting demand from private cars to public transportation. The paper underscores the importance of local community participation in policy-making to ensure equitable and practical solutions. By adopting these economic tools, the EEC can achieve more sustainable urban mobility and improved environmental quality, balancing economic growth with environmental preservation.